A work in progress - Lerner, Jarrett (Aladdin, 2023)
After a bullying incident where Will was first called fat, he just wants to be invisible most days. That's why he hides behind baggy clothes and in the back of the classroom, but he really wishes one person would notice him: his crush, Jules. He knows he doesn't have a chance with Jules, so he decides to change up his eating habits and exercise more in order to lose weight. When that doesn't seem to make a difference, he resorts to increasingly drastic measures to change his appearance. Then, Will meets skateboarder Markus, who helps him see himself in a whole new light.